The Mother of the Believers Umm Salamah and its Jurisprudential Narratives in Reaching Maram from the Guides of Ibn Hajar Al-Ashqalani (Book of Purity) - Al-Dahiree, Rafedh Sabah Abdulwahhab (Journal of Islamic Sciences, 2019)
This research sought show the active role of Muslim women in preserving and documenting the Hadith in promoting the most important pillars of worship (purity), ie purity, and explain their legal status and obligations towards Muslims. This study tackles the legitimate pluralism of purity in different situations, thus enhancing the talk about the role of Muslim women (Umm al-Mu’minin). Umm Salama: (Hind bint Abi Umayyah) in memorizing the hadiths of the Prophet peace be upon him, which relied on several ways in the tabulation of scientific truth separately according to the narratives based in the book (Maram, which examines the provisions of Ibn Hajar al-Asqalani), this study has achieved several Objectives, including highlighting the role of women in the codification of the hadith. This is mentioned in many books of the year, where most of them were specifically combining the provisions and interpretation, literature, supplications, and others, and these books focused on the provisions of purity and worship mentioned by Ibn Hajar al-Ashqalani in his book (Achieving Maram provisions of proof) and includes four responses to the talks to the purity of Umm Salamah, Which includes all positions in purity, such as washing janaabah, menstruation and rituals, and the rule of eating and drinking vessels of gold and silver, as the research methodology consists of summary, introduction, and keywords and theory.